1990
DOI: 10.1104/pp.93.2.611
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for Metabolic Domains within the Matrix Compartment of Pea Leaf Mitochondria

Abstract: The simultaneous oxidation of malate and of glycine was investigated in pea (Pisum sativum) leaf mitochondria. Adding malate to state 4 glycine oxidation did not inhibit, and under some conditions stimulated, glycine oxidation. State 4 oxygen uptake with glycine is restricted because of the control exerted by the membrane potential but reoxidation of NADH by oxaloacetate reduction can still occur. Thus, malate addition stimulates glycine metabolism by producing oxaloacetate. The malate dehydrogenase (EC 1.1.1.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

1992
1992
2015
2015

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(16 citation statements)
references
References 25 publications
0
16
0
Order By: Relevance
“…Binding of NADH to the glycine decarboxylase complex might decrease the amount of free NADH available to other enzymes and be one of the reasons why glycine is preferred over other mitochondrial respiratory substrates (Oliver et al, 1990;Møller, 2001). (1) The oxidation of Gly and malate by pea leaf mitochondria shows rather complex interactions, which have implications for their function in photorespiration (Wiskich et al, 1990). (2) Pea leaf mitochondria contain appreciable amounts of NADP(H), which can also vary significantly in reduction level (Agius et al, 2001;Igamberdiev and Gardeströ m, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Binding of NADH to the glycine decarboxylase complex might decrease the amount of free NADH available to other enzymes and be one of the reasons why glycine is preferred over other mitochondrial respiratory substrates (Oliver et al, 1990;Møller, 2001). (1) The oxidation of Gly and malate by pea leaf mitochondria shows rather complex interactions, which have implications for their function in photorespiration (Wiskich et al, 1990). (2) Pea leaf mitochondria contain appreciable amounts of NADP(H), which can also vary significantly in reduction level (Agius et al, 2001;Igamberdiev and Gardeströ m, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Wiskich et al (34) concluded that the Krebs cycle can operate simultaneously with glycine oxidation by the existence of metabolons, i.e. nonhomogeneous distribution of enzymes or regions of the mitochondria where glycine oxidation enzymes occur and other regions where only the Krebs cycle is operational.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that under illumination NADH production in leaf mitochondria proceeds mainly via glycine decarboxylase, the most important reaction in this organelle (Oliver et al, 1990). NADH is reoxidized via the oxalacetate/malate shuttle system or the respiratory chain to support ATP production, which is also active during the daytime (Wiskich et al, 1990). In the light of these findings the higher levels of GDH and glutamate in family 7-33 than in 8-103 indicate a higher rate of NADH synthesis by glutamate oxidation and the concurrent lower glycine content could indicate a lower rate via glycine decarboxylation.…”
Section: Discussionmentioning
confidence: 99%